High expression of malic enzyme 1 predicts adverse prognosis in patients with cytogenetically normal acute myeloid leukaemia and promotes leukaemogenesis through the IL-6/JAK2/STAT3 pathways - Chang Zhang; Wenlu Li; Fei Wu; Zhongwei Lu; Piaorong Zeng; Zeyu Luo; Yixiong Cao; Feng Wen; Junjun Li; Xi Chen; Fujue Wang (Therapeutic Advances in Hematology)
Background: Progress in improving risk stratification methods for patients with cytogenetically normal acute myeloid leukaemia (CN-AML) remains limited. This study investigates the prognostic significance and potential functional mechanism of malic enzyme 1 (ME1) in CN-AML. Methods: Gene expression and clinical data of patients with CN-AML were obtained from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets, which were subjected to analysis. The prognostic significance of ME1 was assessed through Kaplan–Meier survival analysis, as well as univariate and multivariate Cox regression analyses. A novel risk model based on ME1 expression levels was developed using TCGA data for predicting CN-AML prognosis. Furthermore, the impact of ME1 silencing on AML cell lines was investigated using the Cell Counting Kit-8 assay and flow cytometry. Gene set enrichment analysis (GSEA) analysis and Western blotting were performed to explore the mechanism of ME1 in CN-AML. Results: CN-AML patients expressing higher ME1 levels exhibited shorter event-free survival (EFS) and overall survival (OS) compared to those with lower ME1 expression in the TCGA and multiple GEO datasets (all p < 0.05). Univariate and multivariate Cox regression analyses indicated that ME1 expression served as an independent prognostic factor for the EFS ( p = 0.024 in TCGA, p = 0.035 in GSE6891) and OS ( p = 0.039 in TCGA, p = 0.008 in GSE6891) in patients with CN-AML. The developed risk model demonstrated that patients with CN-AML in the high-risk group had worse survival than those in the low-risk group (hazard ratio: 2.67, 95% confidence interval: 1.54–4.65, p < 0.001) and exhibited strong predictive accuracy for 1-, 3- and 5-year OS (area under the curve = 0.69, 0.75, 0.79, respectively). ME1 knockdown significantly inhibited proliferation and increased apoptosis in AML cells (all p < 0.05). GSEA and Western blotting demonstrated that ME1 regulates the IL-6/JAK2/STAT3 pathway in CN-AML. Conclusion: Elevated ME1 expression serves as an indicator of poorer prognosis in patients with CN-AML, potentially facilitating leukaemogenesis through the IL-6/JAK2/STAT3 pathway. This suggests that ME1 could be a promising prognostic biomarker and therapeutic target for CN-AML.